Quality of life of patients with type II Diabetes Mellitus: Contexts and challenges today (Research, Society and Development, 2024)
This study aimed to investigate the factors that influence the quality of life of patients with Type II Diabetes Mellitus, including medical, psychosocial and socioeconomic aspects, in order to identify effective strategies to improve their quality of life and general well-being. The study consists of a narrative review carried out through an integrative literature review. The bibliographic search for primary articles was conducted from April to May 2023, using the LILACS (Latin American and Caribbean Literature in Health Sciences) and SCIELO (Scientific Electronic Library Online) databases. The results of this research revealed a series of factors that have a significant influence on the quality of life of patients with type II Diabetes Mellitus. Regarding medical aspects, it was observed that adequate glycemic control plays a fundamental role in the quality of life of these patients. Those who were able to maintain blood glucose levels within recommended ranges reported a better quality of life compared to those with inadequate glycemic control. Furthermore, the presence of diabetes-related complications, such as peripheral neuropathy and retinopathy, has been shown to be strongly associated with a decrease in quality of life, highlighting the importance of prevention and early treatment of these conditions.